Non-noble metal nano-porous high-entropy alloy catalyst as well as preparation method and application thereof
Through the preparation of non-precious metal nanoporous high-entropy alloy catalysts, the problems of high cost and low activity of traditional precious metal catalysts are solved, and the effect of efficient hydrodeoxygenation reaction of lignin compounds under mild conditions is achieved.
Patent Information
- Application Number
- CN202411477114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-21
Smart Images

Figure CN119488915A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and relates to a non-precious metal nanoporous high entropy alloy catalyst, a preparation method and an application thereof, and in particular to a non-precious metal nanoporous high entropy alloy catalyst for lignin catalytic conversion, a preparation method and an application thereof. Background Art
[0002] In the past few decades, traditional monometallic or bimetallic catalysts have been the most popular type of catalysts in the field of catalysis, but most of the catalytic systems currently developed rely on precious metal catalysts or commercial catalysts, or are simple improvements on traditional catalysts. The resulting catalytic system has high cost, harsh reaction conditions, low reaction activity, and low catalyst stability. To address the above issues, it is particularly important to develop a highly active non-precious metal catalyst.
[0003] High entropy alloys are composed of 5 or more main metal elements, and the atomic fraction of each main element is greater than 5% and less than 35%. Due to their many ideal properties, high entropy alloys have received great attention in materials and engineering science. The high entropy effect of high entropy alloys breaks the immiscible gap between elements, which is conducive to the rational regulation of element concentration and promotes the optimization of catalytic performance. The inherent synergistic effect of high entropy alloys enables them to improve catalytic activity by doping catalytically active metals. In addition, due to the diversity of elements, there are a large number of possible atomic arrangements on the surface of high entropy alloys, resulting in different adsorption modes of reactants and intermediates. Finely adjusting the surface geometry of high entropy alloys can theoretically maximize the adsorption position of reactants and intermediates, and effectively activate the reactants, thereby obtaining the ideal reaction rate. In recent years, high entropy alloys have also attracted great interest from researchers in the field of catalysis due to their unique microstructure, excellent thermal stability and unique catalytic activity.
[0004] Lignin is an amorphous aromatic polymer widely found in nature. Due to its renewability and "carbon neutrality", lignin is considered to be a green resource that can replace fossil energy to produce bulk and fine chemicals. The structure of lignin platform compounds contains methoxy, phenolic hydroxyl and benzene ring structures. The conversion of lignin platform compounds inevitably involves hydrogenation and deoxygenation reactions. Most traditional biomass catalytic conversion systems face challenges such as harsh reaction conditions, low catalyst activity and poor thermal stability. The field of biomass thermal catalytic conversion has very high requirements for the activity and thermal stability of catalysts, which is also in line with the characteristics of high entropy alloy materials with strong adjustable denaturation and good high-temperature stability, and can give full play to the advantages of high entropy alloy materials. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a non-precious metal nanoporous high entropy alloy catalyst and its preparation method and application. The problem to be solved is how to provide a non-precious metal nanoporous high entropy alloy catalyst and apply it to the hydrodeoxygenation reaction of lignin platform compounds, so that the hydrodeoxygenation reaction of lignin platform compounds can be carried out under milder conditions and end products with different structures can be obtained in high yield.
[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a non-precious metal nanoporous high entropy alloy catalyst, which comprises the following steps:
[0007] S1: mixing aluminum metal powder and transition metal powder in a mass ratio of 1:0.8-1.5, and smelting at a high temperature to obtain a molten metal block;
[0008] S2: crushing the molten metal block obtained in step S1 to obtain molten metal powder;
[0009] S3, ball-milling the smelted metal powder obtained in step S2 under an inert gas protection atmosphere to obtain a ball-milled metal powder;
[0010] S4: adding the ball-milled metal powder into the first solvent, heating and stirring to perform a first reaction, and obtaining a non-precious metal nanoporous high entropy alloy catalyst after separation.
[0011] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0012] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S1, the transition metal is selected from any five of Ni, Cu, Co, Mo, Mn, Fe, Nb and Ti.
[0013] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S1, the combination of transition metals has an atomic fraction ratio of each component greater than 5% and less than 35%.
[0014] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S1, the mass ratio of the aluminum metal powder to the transition metal powder is the mass ratio of the aluminum metal to the sum of all transition metal powders.
[0015] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S1, the smelting temperature range is 900-1300°C.
[0016] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S2, the particle size of the smelted metal powder is <40 mesh.
[0017] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S3, the ball milling conditions are as follows: the material-ball ratio is 1:10-20, the rotation speed is 300-450rpm, and the ball milling time is 2-10h; a grinding aid is also added to the ball mill, and the grinding aid is an organic solvent.
[0018] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S4, the first reaction conditions are: reaction temperature 90°C, reaction time 1 to 3 hours; the first solvent is sodium hydroxide solution, and its concentration is 10-30wt%.
[0019] Preferably, in the aforementioned method for preparing a non-precious metal nanoporous high-entropy alloy catalyst, in step S4, the separation is solid-liquid separation, which includes centrifuging or magnetically adsorbing the mixed solution obtained by the first reaction, removing the solvent, washing it three times with deionized water, and separating it again to obtain a nanoporous high-entropy alloy catalyst.
[0020] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a non-precious metal nanoporous high entropy alloy catalyst, wherein the specific surface area of the non-precious metal nanoporous high entropy alloy catalyst is 72.75-94.66 m 2 / g, pore diameter of 3.64-3.87nm, pore volume of 0.11-0.22ml / g; the non-precious metal nanoporous high entropy alloy catalyst is prepared by the following steps:
[0021] S1: mixing aluminum metal powder and transition metal powder in a mass ratio of 1:0.8-1.5, and smelting at a high temperature to obtain a molten metal block;
[0022] S2: crushing the molten metal block obtained in step S1 to obtain molten metal powder;
[0023] S3, ball-milling the smelted metal powder obtained in step S2 under an inert gas protection atmosphere to obtain a ball-milled metal powder;
[0024] S4: adding the ball-milled metal powder into the first solvent, heating and stirring to perform a first reaction, and obtaining the non-precious metal nanoporous high-entropy alloy catalyst after separation.
[0025] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions: The present invention proposes the use of a non-precious metal nanoporous high entropy alloy catalyst in the hydrodeoxygenation reaction of a lignin model compound 4-propylguaiacol.
[0026] By means of the above technical solution, the present invention provides a non-precious metal nanoporous high entropy alloy catalyst and a preparation method and application thereof, which have at least the following advantages:
[0027] 1. The present invention adopts a smelting-ball milling combination method to prepare high entropy alloys, which helps to improve the specific surface area, particle size and other morphological characteristics of the catalyst;
[0028] 2. The present invention uses a method of removing Al from the alloy by etching with NaOH to construct a porous structure of the catalyst, thereby exposing more active sites;
[0029] 3. The catalyst of the present invention has strong magnetism and is easy to separate and recycle in the process;
[0030] 4. The metal powders used in the present invention are all commercially available non-precious metals, which are cheap and easy to obtain, and easy to expand production;
[0031] 5. The preparation method adopted by the present invention is simple, and the smelting and ball milling methods have low equipment requirements and can be prepared on a large scale;
[0032] 6. The preparation method adopted by the present invention can realize the formation of abundant nano-channels by the catalyst through a simple aluminum removal reaction;
[0033] 7. The high entropy alloy catalyst prepared by the present invention has extremely high hydrodeoxygenation reaction activity. In the hydrodeoxygenation reaction of the lignin model compound 4-propylguaiacol, the main product 4-propylcyclohexanol has a yield and selectivity of more than 88%;
[0034] 8. The high entropy alloy catalyst prepared by the present invention has a specific surface area of 72.75-94.66m 2 / g, the pore diameter is 3.64-3.87nm, and the pore volume is 0.11-0.22ml / g.
[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A flow chart of a method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to some embodiments of the present invention;
[0037] Figure 2 These are SEM images of Example 1 of the present invention and Comparative Example 1 before and after NaOH treatment, wherein a-smelting alloy catalyst; b-smelting alloy powder; c-smelting-ball milling alloy catalyst; d-smelting-ball milling alloy. DETAILED DESCRIPTION
[0038] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a non-precious metal nanoporous high entropy alloy catalyst and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects, in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0039] The following materials or reagents, unless otherwise specified, were commercially available.
[0040] like Figure 1 As shown, some embodiments of the present invention provide a method for preparing a non-precious metal nanoporous high entropy alloy catalyst, which comprises the following steps:
[0041] (1) Preparation of high entropy smelting alloy block: aluminum metal powder and other transition metal powders (including but not limited to Ni, Cu, Co, Mo, Mn, Fe, Nb, Ti) are mixed in proportion, and smelted by arc smelting to obtain a molten metal block; the mass ratio of the aluminum metal powder to the other transition metal powder is 1:0.8-1.5, preferably 1:1;
[0042] Specifically, commercially available aluminum metal powder and other transition metal powders are mixed and added into a smelting mold, heated and stirred to be fully mixed, and then cooled and demolded to obtain a molten metal block.
[0043] In this step, the heating method is arc melting, the melting current is 300-700A, and the melting time is 3-10 minutes, so that the metal can be fully melted; if the time is less than 3 minutes, the short melting time will lead to insufficient melting; if the time is greater than 10 minutes, the melting time is too long and the alloy quality will be lost; the number of flipping is 3-6 times, so that the metal is mixed evenly and the heating is uniform; if it is less than 3 times, the number of flipping is too small, resulting in uneven mixing of the metal; if it is greater than 6 times, too many times lead to insufficient heating, and the cooling method is natural cooling;
[0044] The mass ratio of the aluminum metal powder to the transition metal powder is the ratio of the mass of aluminum metal to the sum of the masses of all transition metal powders;
[0045] The transition metal includes but is not limited to any five of Ni, Cu, Co, Mo, Mn, Fe, Nb, and Ti. For example, it can be a combination of Ni, Cu, Co, Mo, and Mn or a combination of Ni, Mo, Mn, Fe, Nb, and Ti.
[0046] The ratio of each component of the transition metal combination is controlled by the mass of the added metal powder to have an atomic fraction of ≥5% and ≤35%. This ratio range is selected to ensure that the content of each element is within the range specified in the definition of high entropy alloy.
[0047] (2) crushing the smelted metal block by an ore crusher to obtain smelted metal powder, wherein the particle size of the metal powder is less than 40 mesh;
[0048] Specifically, the metal block obtained after smelting is placed in an ore crusher for crushing, and an organic solvent is added as a grinding aid. The product obtained after crushing is passed through a 40-mesh sieve, and particles with a particle size of less than 40 mesh are retained to obtain smelted metal powder.
[0049] In this step, the organic solvent used can be selected from one of methanol, ethanol, n-heptane and n-hexane. The addition of the organic solvent can act as a grinding aid to prevent metal agglomeration, promote the refinement and alloying of metal powders, and prevent cold welding. The amount of the grinding aid added accounts for 5-10% of the mass of the metal block. When it is greater than 10%, too much grinding aid affects the ball milling effect, and when it is less than 5%, too little grinding aid cannot play a grinding aid effect.
[0050] (3) In an inert gas atmosphere, the molten metal powder is ball-milled to obtain a ball-milled metal powder.
[0051] Specifically, a certain amount of smelted metal powder is weighed and placed in a ball mill, an organic solvent is added as a grinding aid, an inert gas is introduced into the ball mill to protect the inert gas atmosphere, and ball milling is performed to obtain ball milled metal powder.
[0052] In this step, the material-to-ball ratio during ball milling is 1:10-20; if the material-to-ball ratio is less than 1:20, cold welding will occur due to excessive grinding balls, resulting in a decrease in yield, and more wear will easily lead to impurities mixing; if the material-to-ball ratio is greater than 1:10, the grinding balls will have less contact with the metal, resulting in insufficient ball milling and insufficient alloying; the rotation speed is 300-450rpm, if the rotation speed is less than 300rpm, the rotation speed is too low, which will lead to weak impact, shear, friction and other forces when the grinding balls and metal are in contact, affecting the alloying effect; if the rotation speed is greater than 450rpm, the rotation speed is too high, resulting in extremely high energy on the contacting surface, which is prone to cold welding; the ball milling time is 2-10h, if it is less than 2h, the ball milling time is too short and the alloying is insufficient; if it is greater than 10h, the time is too long and cold welding will occur.
[0053] The inert gas is argon or nitrogen (purity>99%). Through the protection of the inert gas, the oxidation of the ball-milled powder by air can be prevented.
[0054] The organic solvent can be selected from one of methanol, anhydrous ethanol, n-heptane and n-hexane; the addition of the organic solvent can act as a grinding aid to prevent metal agglomeration, promote the refinement and alloying of metal powders, and prevent cold welding.
[0055] (4) adding the ball-milled metal powder into a first solvent, heating and stirring to perform a first reaction, and obtaining the non-precious metal nanoporous high-entropy alloy catalyst after separation. The first solvent is a sodium hydroxide solution, and the first reaction is an aluminum removal reaction;
[0056] Specifically, the obtained ball-milled metal powder is added to a NaOH solution, heated and stirred to fully carry out the aluminum removal reaction. After the reaction is completed, the reaction solvent is separated and removed, and washed with deionized water until the washing liquid is neutral to obtain the non-precious metal nanoporous high-entropy alloy catalyst.
[0057] In this step, the concentration of the NaOH solution is 10-30wt%. Within this concentration range, a rich porous structure can be formed while having less toxic effect on the catalyst. If the concentration is less than 10wt%, the concentration is too low, resulting in incomplete aluminum removal, which reduces the specific surface area of the catalyst and reduces the catalytic activity. If the concentration is greater than 30wt%, the concentration is too high, which will corrode the catalyst and cause deactivation.
[0058] The conditions of the first reaction are as follows: the reaction temperature is 70-100°C; if the temperature is lower than 70°C, the reaction temperature is too low, which will result in a too slow reaction rate for aluminum removal; if the temperature is higher than 100°C, the excessively high temperature will accelerate atomic movement, increase the tendency of the catalyst's surface structure to rearrange, and affect the stability of the porous structure; the reaction time is 1 to 3h, if it is less than 1h, the reaction time is too low, resulting in incomplete aluminum removal; if it is greater than 3h, the reaction time is too long, and alkaline etching has a toxic effect on the catalytic sites.
[0059] The separation step is solid-liquid separation, and the catalyst and the solvent are separated by centrifugation or magnetic separation.
[0060] In summary, compared with traditional non-precious metal catalysts, the non-precious metal nanoporous high entropy alloy catalyst proposed in the present invention has better hydrodeoxygenation activity and selectivity for cyclohexanol compounds, and the catalyst preparation process is relatively simple and has low equipment requirements. Therefore, the non-precious metal nanoporous high entropy alloy catalyst for biomass catalytic conversion proposed in the present invention is more in line with the actual needs of chemical production, has the characteristics of adjustable design and optimization of different catalysts and reaction systems, and is also suitable for developing a variety of efficient catalytic systems for different products.
[0061] Some embodiments of the present invention further provide a non-precious metal nanoporous high entropy alloy catalyst, wherein the specific surface area of the nanoporous high entropy alloy catalyst is 72.75-94.66 m 2 / g, the pore diameter is 3.64-3.87nm, and the pore volume is 0.11-0.22ml / g; the nanoporous high entropy alloy catalyst is prepared by the above method.
[0062] Some embodiments of the present invention also provide a use of a non-precious metal nanoporous high entropy alloy catalyst in the hydrodeoxygenation reaction of a lignin model compound 4-propylguaiacol.
[0063] Furthermore, the use of the non-precious metal nanoporous high entropy alloy catalyst in the hydrodeoxygenation reaction of the lignin model compound 4-propylguaiacol comprises the following steps:
[0064] a. Wash the non-precious metal nanoporous high entropy alloy catalyst with deionized water for at least three times to ensure that the non-precious metal nanoporous high entropy alloy catalyst is washed to a neutral pH value.
[0065] b Subsequently, the non-precious metal nanoporous high entropy alloy catalyst is transferred to a fixed bed reactor and the reactor is rinsed with isopropanol, which is repeated at least three times to ensure that the water retained in the non-precious metal nanoporous high entropy alloy catalyst is removed.
[0066] The reaction substrate 4-propylguaiacol is weighed, and the mass ratio of the reaction substrate 4-propylguaiacol to the catalyst is 1 to 15:1. When the mass ratio is lower than 1:1, the catalyst ratio is too high, and the reaction by-products increase. When the mass ratio is higher than 15:1, the catalyst ratio is too low, and the reaction is insufficient. The preferred ratio of the substrate to the catalyst is 1:1. The 4-propylguaiacol is dissolved in isopropanol and stirred thoroughly to form a solution. The concentration of the solution is between 1 g / 100 ml and 10 g / 100 ml. When the mass ratio is lower than 1 g / 100 ml, the concentration is too low, the substrate is less, and the yield is low. When the mass ratio is higher than 10 g / 100 ml, the concentration is too high, and the reaction substrate cannot be completely reacted in the fixed bed.
[0067] c. Operate the fixed bed reactor to react at 160-200°C and 0-3MPa hydrogen pressure. When the temperature is lower than 160°C, the hydrogenation reaction cannot be completed. When the temperature is higher than 200°C, it will lead to over-reaction and generate by-products. After the reaction is completed, collect the post-reaction solution to obtain 4-propylcyclohexanol with a yield of 80%-90%.
[0068] The specific implementation methods of the present invention are further described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0069] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0070] Industrial pure metals (Ni, Cu, Co, Fe, Mo powders) with a purity of more than 99.9% by mass are selected as raw materials.
[0071] Example 1
[0072] This embodiment provides a non-precious metal nanoporous high entropy alloy catalyst, which is a high entropy alloy composed of Ni, Cu, Co, Fe, and Mo elements. The amount of its components is shown in Table 1. The preparation method thereof is as follows:
[0073] S1, weigh 50g Al, 10g Ni, 10g Cu, 10g Co, 10g Fe, 10g Mo for smelting, using arc smelting, the smelting current is 700A, the smelting time is 3min, and the smelting is turned over 6 times;
[0074] S2, placing the metal block obtained in step S1 into an ore crusher, adding anhydrous ethanol accounting for 10% of the mass of the metal block as a grinding aid. Then crushing, passing the crushed metal through a 40-mesh sieve, selecting powder with less than 40 mesh, and obtaining smelting powder;
[0075] S3, placing the smelted powder obtained in step S2 in a ball mill with a material-to-ball ratio of 1:15, adding anhydrous ethanol accounting for 10% of the mass of the metal block as a grinding aid, introducing high-purity argon gas with a purity of 99.9% as a protective gas, the ball milling speed is 400 rpm, the ball milling time is 4 hours, and ball milled powder is obtained after ball milling;
[0076] S4, take 1g of ball-milled powder, add it to 10wt% NaOH solution in 10 times within two minutes, and react at 90°C for 1h. After the reaction, use a magnet to adsorb the catalyst until there are no black catalyst particles in the solution, remove the remaining reaction solution, and then wash the catalyst with deionized water for multiple times until the washing solution is neutral.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is that the concentration of the NaOH solution in step S4 of this embodiment is 20 wt %, and the remaining steps and parameters are the same as those in embodiment 1.
[0079] Example 3
[0080] The difference between this embodiment and embodiment 1 is that the concentration of the NaOH solution in step S4 of this embodiment is 30 wt %, and the remaining steps and parameters are the same as those in embodiment 1.
[0081] Comparative Example 1
[0082] The difference between Comparative Example 1 and Example 1 is that this comparative example does not have step S3, and the remaining steps and parameters are the same as those of Example 1.
[0083] Comparative Example 2
[0084] The difference between Comparative Example 2 and Example 1 is that this comparative example does not have step S3, the concentration of the NaOH solution in step S4 is 20wt%, and the remaining steps and parameters are the same as those in Example 1.
[0085] Comparative Example 3
[0086] The difference between Comparative Example 3 and Example 1 is that the ball milling operation in step S3 is not performed in this comparative example, the concentration of the NaOH solution in step S4 is 30 wt %, and the remaining steps and parameters are the same as those in Example 1.
[0087] Table 1 Processing conditions and structural performance of Examples 1-3 and Comparative Examples 1-3
[0088]
[0089] From the data in Table 1, it can be seen that the specific surface areas of the catalysts of Examples 1-3 of the present invention are 72.75-94.66 m 2 / g, pore diameter is 3.64-3.87nm, pore volume is 0.11-0.22ml / g; the catalyst after ball milling is superior to the catalyst without ball milling in structural performance, and the specific surface area of the catalyst after ball milling is much larger than that of the catalyst without ball milling. It can be seen from Example 1 and Comparative Example 1 that the specific surface area of Example 1 after ball milling is 94.66m 2 / g, much higher than the unmilled comparative example 1 (77.86m 2 / g), confirming that ball milling helps to increase the specific surface area of the catalyst, which is crucial for catalytic activity and provides more active sites for the reaction.
[0090] pass Figure 2 It can be seen that the ball-milled Example 1 (ball-milled alloy catalyst) has a smaller particle size and a more regular morphology than the un-ball-milled Comparative Example 2, and the alloying effect is significant. Comparing the morphology of the alloy powder before and after the NaOH solution treatment, it is found that the particle size of the alloy powder after ball milling is much smaller than that of the smelted alloy powder. In addition, the particle size of the alloy powder after ball milling is also more uniform.
[0091] Table 2 Al removal rate of Example 1 and Comparative Example 1 after NaOH treatment
[0092] NaOH mass concentration Ball milling Al removal rate Example 1 10% ball milling 83.97% Comparative Example 1 10% 90.67% Example 2 20% ball milling 90.81% Comparative Example 2 20% 94.60%
[0093] Table 2 compares the effect of NaOH treatment on Al removal in the alloy. The results show that the Al removal rate of catalyst Example 1 after ball milling is 83.97%, which is significantly lower than that of the unmilled catalyst comparative example 1 (90.67%). This indicates that the catalyst after ball milling has strong corrosion resistance to NaOH, and different metals have better alloying after ball milling. It also indicates that the alloy after ball milling has strong corrosion resistance, and the obtained catalyst will have better stability.
[0094] Application Examples
[0095] 1 g of the catalyst in Example 1 (wet weight, with a water content of 50 wt%) was weighed and filled into a fluidized bed reactor, and a 1 g / 100 ml isopropanol solution of 4-propylguaiacol was prepared as a substrate, and 3 MPa of H2 was introduced to generate (see Formula I), and the catalyst activity was tested at different temperatures. The liquid product was analyzed by gas chromatography, and the analysis results are shown in Table 3.
[0096] Gas chromatography conditions: GC7890A gas chromatograph, FID detector, capillary column (HP-5), programmed temperature, starting at 40°C, maintained for 3 min, then increased to 300°C at a heating rate of 10°C / min and maintained for 2 min.
[0097]
[0098] Among them, A: 4-propylguaiacol, B: propylbenzene, C: 4-ethylcyclohexanol, D: 4-ethylphenol, E: 2-methoxy-4-propylcyclohexanol
[0099] Table 3 Hydrodeoxygenation activity test of high entropy alloy catalyst of Example 1
[0100]
[0101] The activity test results of the catalysts in Table 3 show that the catalyst has a high hydrodeoxygenation activity for the lignin model 4-propylguaiacol, and has a high selectivity for 4-propylcyclohexanol. When the temperature reaches 180°C, the target product of hydrodeoxygenation, 4-propylcyclohexanol, has a selectivity of 90% and a yield of more than 88%, proving that the catalyst has an extremely high hydrodeoxygenation activity.
[0102] 1g of commercial porous nickel catalyst Raney Ni (wet weight, with a water content of 50wt%) was weighed and filled into a fluidized bed reactor, and 1g / 100ml of 4-propylguaiacol isopropanol solution was prepared as a substrate, and 3MPa H2 was introduced to generate a product shown in Formula I, and the catalyst activity test was performed at different temperatures. The liquid product was analyzed by gas chromatography, and the analysis results are shown in Table 4. The preparation process of the porous nickel catalyst Raney Ni is to melt the metal powder Ni:Al=1:1 mass ratio, and then obtain the commercial catalyst by dealumination reaction in step S4.
[0103] Gas chromatography conditions: GC7890A gas chromatograph, FID detector, capillary column (HP-5), programmed temperature, starting at 40°C, maintained for 3 min, then increased to 300°C at a heating rate of 10°C / min and maintained for 2 min.
[0104] Table 4 Hydrodeoxygenation activity test of commercial porous nickel catalyst Raney Ni
[0105]
[0106]
[0107] The activity test results of the catalysts in Table 4 show that the commercial porous nickel catalyst also has a certain hydrodeoxygenation activity for the lignin model 4-propylguaiacol, but the activity is lower than that of the catalyst used in the present invention in Table 3. Under the same reaction conditions (180° C., 0.5 ml / min), the catalytic yield of the catalyst prepared in Example 1 can reach 88%, while that of the commercial catalyst is only 81%. At the same time, the catalyst prepared by the present invention has better stability and higher selectivity for the product 4-propylcyclohexanol.
[0108] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0109] The numerical range described in the present invention includes all the numerical values within the range, and includes the range value formed by any two numerical values within the range. Different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0110] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a non-precious metal nanoporous high entropy alloy catalyst, characterized in that: The following steps are involved: S1: mixing aluminum metal powder and transition metal powder in a mass ratio of 1:0.8-1.5, and smelting at a high temperature to obtain a molten metal block; S2: crushing the molten metal block obtained in step S1 to obtain molten metal powder; S3, ball-milling the smelted metal powder obtained in step S2 under an inert gas protection atmosphere to obtain a ball-milled metal powder; S4: adding the ball-milled metal powder into the first solvent, heating and stirring to perform a first reaction, and obtaining the non-precious metal nanoporous high entropy alloy catalyst after separation.
2. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: In step S1, the transition metal is selected from any five of Ni, Cu, Co, Mo, Mn, Fe, Nb and Ti.
3. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: In step S1, the combination of transition metals has an atomic fraction ratio of each component greater than 5% and less than 35%.
4. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: In step S1, the ratio of the aluminum metal powder to the transition metal powder is the ratio of the aluminum metal to the sum of all transition metal powders.
5. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: In step S1, the smelting temperature range is 900-1300°C; in step S2, the particle size of the smelted metal powder is less than 40 mesh.
6. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: In step S3, the ball milling conditions are as follows: the material-ball ratio is 1:10-20, the rotation speed is 300-450 rpm, and the ball milling time is 2-10 hours; a grinding aid is also added to the ball mill, and the grinding aid is an organic solvent.
7. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: The first reaction conditions are: reaction temperature 90° C., reaction time 1-3 hours; the first solvent is sodium hydroxide solution, and its concentration is 10-30wt%.
8. The method for preparing a non-precious metal nanoporous high entropy alloy catalyst according to claim 1, characterized in that: The separation is solid-liquid separation, which includes removing the solvent from the mixed solution obtained by the first reaction by centrifugation or magnetic adsorption, washing it three times with deionized water, and separating it again to obtain a non-precious metal nanoporous high-entropy alloy catalyst.
9. A non-precious metal nanoporous high entropy alloy catalyst, characterized in that: The specific surface area of the non-precious metal nanoporous high entropy alloy catalyst is 72.75-94.66m 2 / g, pore diameter of 3.64-3.87nm, pore volume of 0.11-0.22ml / g; the non-precious metal nanoporous high entropy alloy catalyst is prepared by the following steps: S1: mixing aluminum metal powder and transition metal powder in a mass ratio of 1:0.8-1.5, and smelting at a high temperature to obtain a molten metal block; S2: crushing the molten metal block obtained in step S1 to obtain molten metal powder; S3, ball-milling the smelted metal powder obtained in step S2 under an inert gas protection atmosphere to obtain a ball-milled metal powder; S4: adding the ball-milled metal powder into the first solvent, heating and stirring to perform a first reaction, and obtaining the non-precious metal nanoporous high entropy alloy catalyst after separation.
10. Application of a non-precious metal nanoporous high entropy alloy catalyst in the hydrodeoxygenation reaction of the lignin model compound 4-propylguaiacol.
Citation Information
Cited By
High-entropy sulfide catalyst, preparation method thereof and lignin depolymerization electro-catalysis method
CN121610827A